Waqf, Shared Value and the Rise of Society Governance - Afifi, Abdullah A (IDRIS Darulfunun Institute, 2025)
This article advances the argument that waqf (Islamic endowment) constitutes a foundational model of society governance, in which communities institutionalize moral responsibility into durable public capacity. Rather than viewing waqf solely as a charitable or financial instrument, the study conceptualizes it as a governance architecture that enables societies to mobilize, preserve, and deploy resources for collective welfare independent of fluctuating political regimes. Through a narrative-historical analysis, the article traces waqf’s evolution from the Prophetic model of trust-based stewardship and the institutional consolidation under the early caliphs, to its resilience during dynastic centralization, its fiscal institutionalization in the Ottoman period, and its contemporary transformation within modern regulatory frameworks. Central to the analysis is the proposition that waqf embodies an early and enduring form of shared value creation. By preserving endowed capital while continuously generating social returns, waqf integrates economic sustainability with public benefit. This dual function positions waqf as a bridge between moral economy and modern governance theory, aligning closely with contemporary debates on stakeholder capitalism, sustainable development, and civil society resilience. The article further argues that waqf is more than its challenges. While issues of governance reform, transparency, and asset optimization remain significant, these represent transitional adjustments rather than structural weaknesses. Properly institutionalized, waqf strengthens community autonomy, enhances accountability through trusteeship, and sustains intergenerational responsibility. In an era marked by fiscal strain and institutional distrust, waqf offers a society-centered governance paradigm capable of generating shared value and reinforcing collective capacity beyond the limits of state and market mechanisms.